2007
DOI: 10.1111/j.1530-0277.2007.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Level, Neighborhood Social Disorder, and Mutual Intimate Partner Violence

Abstract: Drinking level and neighborhood characteristics should be taken into account when assessing risk for mutual IPV among married/cohabiting men and women in the general population. An environmental approach to IPV prevention and intervention which addresses the neighborhood context in which couples reside may be a promising strategy for reducing IPV occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 58 publications
10
102
2
1
Order By: Relevance
“…26,27 IPV was associated with harmful use of alcohol (measured by binge drinking and AUD), particularly in men (victim or perpetrator), in agreement with previous studies showing evidence that alcohol use by one or both partners contributes to the risk and severity of IPV. 28,29 This result also replicates our previous publication based on the 2006 dataset alone. 30 Additionally, male-to-female IPV perpetration has been consistently linked to heavy drinking by men 31 and AUD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…26,27 IPV was associated with harmful use of alcohol (measured by binge drinking and AUD), particularly in men (victim or perpetrator), in agreement with previous studies showing evidence that alcohol use by one or both partners contributes to the risk and severity of IPV. 28,29 This result also replicates our previous publication based on the 2006 dataset alone. 30 Additionally, male-to-female IPV perpetration has been consistently linked to heavy drinking by men 31 and AUD.…”
Section: Discussionsupporting
confidence: 81%
“…It must be highlighted that only a few studies so far have specifically investigated bidirectional violence; however, the risk factors mentioned have been identified beforesuch as alcohol, tobacco, and illegal drug use. 29,35 Okuda et al 38 have shown that across an extensive variety of factors, the strongest association with violence perpetration is victimization itself, leading to a cycle of escalating violence. Taken together, the present results and the literature about bidirectional IPV indicate that individuals affected by bidirectional violence tend to suffer the most.…”
Section: Discussionmentioning
confidence: 99%
“…Although some researchers find no differences between mutually violent and perpetrator or victim-only couples in terms of alcohol use (Caetano et al, 2008;Lewis et al, 2002), others report that drinking is a risk factor for bidirectional violence. Males and females who reported binge drinking in the past month were at an increased risk for mutual IPV among a national sample of cohabiting and married adults (Cunradi, 2007). El-Bassel, Wu, Go, and Hill (2005) found that although frequent crack and marijuana use increased the likelihood of subsequent physical and sexual IPV, the findings were inconclusive for cocaine, heroin, and frequent binge drinking.…”
Section: Substance Usementioning
confidence: 97%
“…Alternatively, some researchers find that men and women use approximately equal levels of violence toward one another and report similar levels of victimization (Anderson, 2002;Harned, 2002;Robertson & Murachver, 2007;Straus, 2008). Cunradi (2007), for example, found that approximately the same proportion of men (3.1%) and women (3.2%) reported experiencing mutual IPV.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation